2009
DOI: 10.1007/s00296-008-0833-z
|View full text |Cite
|
Sign up to set email alerts
|

Single center prospective study of tacrolimus efficacy and safety in treatment of rheumatoid arthritis

Abstract: The aim of this study was to prospectively evaluate the efficacy and safety of tacrolimus for treating rheumatoid arthritis (RA) patients in clinical practice. Fifty-five active RA patients who had been resistant or intolerant to other disease-modifying antirheumatic drugs were enrolled in this open-label trial. Patients were administered tacrolimus at a dosage of 1, 2 or 3 mg once daily, and followed up for 24 weeks. They were divided into three groups according to their dosage. Efficacy and safety were evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 12 publications
2
13
0
Order By: Relevance
“…We were able to conWrm a drug response for these manifestations at 4 weeks, the same as in our report on RA [16]. Our results also indicate that it possesses steroid-sparing eVects and makes a good combination partner in a subgroup of patients that responded well to the therapy.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We were able to conWrm a drug response for these manifestations at 4 weeks, the same as in our report on RA [16]. Our results also indicate that it possesses steroid-sparing eVects and makes a good combination partner in a subgroup of patients that responded well to the therapy.…”
Section: Discussionsupporting
confidence: 88%
“…In 2004, the use of TAC for the treatment of rheumatoid arthritis (RA) had been approved in Canada and Japan. A great deal of clinical evidence was accumulated, including our reports on RA [13][14][15][16]. More recently, in 2006, TAC was approved for lupus nephritis with intolerance to be the previously normal treatment in Japan, Wrst in the world.…”
Section: Introductionmentioning
confidence: 99%
“…The prednisolone dose was tapered by 5 to 10 mg/day until the dose reached to 20 mg/day, after that it was reduced by 2.5 mg/day until a maintenance dose of 10 mg/day was reached. To justify the tacrolimus dose, we referred to a prospective study of tacrolimus efficacy and safety in the treatment of rheumatoid arthritis [20]. The efficacy and safety have been confirmed when patients with rheumatoid arthritis were administered tacrolimus at a dosage of 3 mg once a day in the evening.…”
Section: Methodsmentioning
confidence: 99%
“…Recent cases of lupus nephritis and adultonset Still's disease were successfully treated using TAC; in those cases, CAM was administered in order to increase the concentration of TAC in the blood (9,10). Suzuki et al measured the concentration of TAC in the blood of patients with RA, and they found that the concentration of TAC in the blood was 2.96 ng/ mL in patients receiving a dose of 1 mg/day, 4.29 ng/ mL in patients receiving a dose of 2 mg/day, and 8.32 ng/mL in patients receiving a dose of 3 mg/day (11). However, the concentration varied widely in individual patients in those three groups.…”
Section: (Received July 19 2017; Revisedmentioning
confidence: 99%